2016
DOI: 10.1503/cmaj.151059
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the influenza vaccine in preventing admission to hospital and death in people with type 2 diabetes

Abstract: Background:The health burden caused by seasonal influenza is substantial. We sought to examine the effectiveness of influenza vaccination against admission to hospital for acute cardiovascular and respiratory conditions and all-cause death in people with type 2 diabetes. Methods:We conducted a retrospective cohort study using primary and secondary care data from the Clinical Practice Research Datalink in England, over a 7-year period between 2003/04 and 2009/10. We enrolled 124 503 adults with type 2 diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 29 publications
(41 reference statements)
1
72
1
2
Order By: Relevance
“…Another study demonstrated that influenza vaccination, apart from reducing the risk of influenza and its complications, was associated with lower hospital admission rates: 15% for pneumonia or influenza, 19% for acute myocardial infarction, 22% for heart failure and 30% for stroke. the study also revealed a 24% lower all-cause mortality in vaccinated vs nonvaccinated patients [32]. A study conducted in the netherlands during the 1999-2000 influenza A epidemic in a population of adults with diabetes found that vaccination was associated with a 56% reduction in any complication, a 54% reduction in hospitalizations, and a 58% reduction in deaths [33].…”
Section: Patients With Diabetes Mellitusmentioning
confidence: 83%
“…Another study demonstrated that influenza vaccination, apart from reducing the risk of influenza and its complications, was associated with lower hospital admission rates: 15% for pneumonia or influenza, 19% for acute myocardial infarction, 22% for heart failure and 30% for stroke. the study also revealed a 24% lower all-cause mortality in vaccinated vs nonvaccinated patients [32]. A study conducted in the netherlands during the 1999-2000 influenza A epidemic in a population of adults with diabetes found that vaccination was associated with a 56% reduction in any complication, a 54% reduction in hospitalizations, and a 58% reduction in deaths [33].…”
Section: Patients With Diabetes Mellitusmentioning
confidence: 83%
“…After adding 2 studies identified through manual searches, a total of 11 studies were included in the final analysis. Of 3 studies sampled from the United Kingdom General Practice Research Database, 2 studies included overlapping groups of participants [22,23]; we used data from each study in overall and subgroup analyses as appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…As a secondary prevention measure, anti-influenza vaccination may be considered in type 2 diabetic patients with a higher predisposition to cardiovascular diseases [40]. Notably, admissions for HF were significantly reduced in the flu season in vaccine recipients compared to those who did not receive the vaccine.…”
Section: Anti-influenza Vaccination and Heart Failurementioning
confidence: 99%